Educational Value of a 3D Printer in Ophthalmology Training - Arshad, Jawad; Helms, Richard W.; Orge, Faruk H.; Sayegh, Rony R. (Journal of Academic Ophthalmology, 2018)
Three-dimensional (3D) printers are increasingly being used in medicine for surgical planning, medical education, patient education, research, and device development. We explore the educational value of a 3D printer for trainees in an ophthalmology residency program. A 3D printer was made available to medical students, residents, and clinical and research fellows in the Department of Ophthalmology at Case Western Reserve University. One of the medical students was proficient in the technology and was available to help. Multiple projects were initiated including the manufacturing of slit-lamp cellphone adapters and various interface and integral custom-made parts for research applications. The 3D printer was found to be useful by 20 of 21 trainees surveyed with 17 of 20 saying they would use it after graduation if they had access to one. All the respondents felt that the availability of the technology can contribute to increased innovation in the ophthalmology department. We encourage other ophthalmology departments to experiment with 3D printing as a tool to foster innovation and creativity for trainees.
Keywords: 3D printing; residency; education; ophthalmology; slit-lamp; cellphone; ultrasound biomicroscopy